2007
DOI: 10.1590/s1807-59322007000200002
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of the Treatment of Infected Hip Arthroplasties With or Without the Use of an Antibiotic-Loaded Cement Spacer

Abstract: 0.05). The average leg length discrepancy was 2.6 cm in the control group and 1.5 cm in the study group (P < 0.05). The patients treated with a spacer had better clinical results (81.5% of patients with good results against 60.0% for the control group). CONCLUSION: The use of an antibiotic-loaded spacer in the 2-stage treatment of infected hip arthroplasties provides better infection control with good functional results and is superior to treatment in 2 stages without a spacer. Level of Evidence: Therapeutic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 45 publications
2
98
0
2
Order By: Relevance
“…Baseline demographic information of cases and controls is shown in Table 1. For cases, the median duration from joint insertion until first debridement (joint age) was 14 days (interquartile range (IQR) [12][13][14][15][16][17][18][19][20]. The median duration of symptoms until debridement was 4 days (IQR 3-9).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Baseline demographic information of cases and controls is shown in Table 1. For cases, the median duration from joint insertion until first debridement (joint age) was 14 days (interquartile range (IQR) [12][13][14][15][16][17][18][19][20]. The median duration of symptoms until debridement was 4 days (IQR 3-9).…”
Section: Resultsmentioning
confidence: 99%
“…This improvement was not significantly different to that seen in control patients with no PJI and is similar to results of +33 and +39.1 reported in two previous studies examining treatment of PJI with mainly prosthesis exchange. 15,16 Other studies have reported mean post-treatment HHS after treatment of PJI with prosthesis exchange at between 69 and 84 17 and after debridement and prosthesis retention at 79. 9 The mean post-arthroplasty HHS of 68.5 seen in cases in this study is at the lower end of these scores; however, adequate comparison is difficult as these studies do not report pre-arthroplasty HHS and administered the score much later than in this study.…”
Section: Discussionmentioning
confidence: 99%
“…In studies of well-characterized bacterial strains [12,31,49] and clinical bacterial isolates from biofilmbased infections [6,45,48,54], the antimicrobial concentration required to kill bacteria in biofilms can be 100 to 1000 times greater than the minimum inhibitory concentration for the planktonic form. Because the antimicrobial concentrations required to manage biofilm often exceed the concentrations at which systemic toxicity is prohibitive, surgical débridement and local antimicrobial delivery are necessary [10,13,14,56].…”
Section: Introductionmentioning
confidence: 99%
“…As infecções que se manifestem após esse período, devido à formação de biofilme e aderência bacteriana ao material implantado, devem ser tratadas com limpeza cirúrgica extensa associada à remoção da prótese articular, que pode ser substituída em um ou dois tempos. Neste caso, o tempo total de administração dos antibióticos é de seis meses (7,10) . Os fluxogramas abaixo sintetizam as recomendações atuais no manejo destas infecções (Figuras 3 e 4).…”
Section: Tratamentounclassified
“…Os maiores índices de sucesso terapêutico que chegam a 93% referem-se à retirada da prótese infectada associada a antibioticoterapia prolongada que deverá ser escolhida baseada no agente etiológico isolado na cirurgia de retirada, com posterior implante de nova pró-tese em segundo tempo cirúrgico, geralmente seis a oito semanas após (7,10) . O cimento de polimetilmetacrilato impregnado com gentamicina ou tobramicina pode ser empregado nos reimplantes de próteses após infecções.…”
Section: Tratamentounclassified